Trends and Developments in the European Financial Sector - Eleftherios Thalassinos (European Financial and Accounting Journal, 2008)
The international tendency towards the deregulation of restrictions and administrative settlements has suppressed the barriers between national financial markets. The adoption of a common currency and the rapid spread of new technologies lead to intense competition, imposing the acceleration of reformations in the European financial sector. Financial institutions have consequently adjusted their strategies, in order to confront the challenges and exploit the opportunities of new developments. In this work, a review of strategies that have been applied by financial institutions in the most important European markets is presented, as well as the repercussions of those strategies on the structure of the European financial sector. The controversial question is which form of affiliation will allow them to encounter successfully the expected intensity of international financial competition.
Keywords: E5; G2; G34; 650; European financial system; Deregulation; Structural change; Mergers and acquisitions; Regulating barriers; Cross-border extension